A day in the life of frontline manufacturing personnel: A diary-based safety study. (December 2020) - Pickup, Sarah; Paton, Kevin; Hayes, Catherine; Morrison, Ben
Highlights: Diaries captured time sensitive human factors information that would otherwise not usually captured. Skill based errors were the most frequently occurring type of human error. Situational characteristics were associated with 77% of all recorded errors. The least prevalent recorded form of human error was violations. Abstract: Recorded incidences of work-related illness and injury within the manufacturing sector remain significantly high, therefore, an awareness of the aetiology of accidents remains integral to any realistic prospect of safety improvement interventions within this complex industry. The epistemological stance adopted in safety behaviour development in research design and execution has largely focused on empirical outcome-based studies. Using personalised individual diaries to record real time data of safety-related events, including social cognitive contextual details, this study, for the first time qualitatively explores employee recorded incidents, permitting the identification of perceived latent conditions belying cognitive errors. The study revealed the most frequently occurring incident types were unsafe acts (38%) followed by unsafe conditions (28%), with a greater proportion of near misses (N = 46) in comparison to actual accidents (N = 13). Also apparent were inconsistencies in formal and informal reporting processes. Skill based errors were the most prevalent recorded human error type associated with distraction, alongside incompatible work environments. Violations were evident, to a lesser degree of recordable incidents. Across all human error types, qualitative accounts of safety climate concepts including leader violations and quality of leadership were described. The study thus made possible the capture of day-to-day safety behaviours and conditions, illuminating new perspectives on meaningful issues at both individual and systems levels. Adopting a systematically tailored approach to the exploration of suboptimal safety behaviour aetiology, there is a greater likelihood of knowledge acquisition of incidents or symptoms at an organisational level, which are then equipped to reflexively respond with a tailored address of these issues 'in situ'.